2014
DOI: 10.1159/000365090
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Hydration in the Prevention of Contrast-Induced Acute Kidney Injury in Patients Undergoing Coronary Angiography or Intervention

Abstract: Background: Efficacy of intravenous (IV) volume expansion in preventing contrast-induced acute kidney injury (CI-AKI) is well known. However, the role of oral hydration has not been well established. The aim of this work was to evaluate the efficacy of oral hydration in preventing CI-AKI. Methods: We prospectively randomized 225 patients undergoing coronary angiography and/or percutaneous coronary intervention in either oral hydration or IV hydration groups. Patients who have at least one of the high-risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
2
17
0
4
Order By: Relevance
“…The incidence of CIN was 6.9% in the drinking water group and 7.3% in the physiological saline group, and no significant difference was found between the two groups. 210 In a study on patients with normal renal function (SCr <110 μmol/L≈1.24 mg/dL) undergoing scheduled CAG or PCI, the preventive effect of the administration of 1 mL/kg/h of physiological saline solution 12 h before and 24 h after the procedure on CIN onset was compared to two drinking load groups (one group who received 500 mL of tap water for 2 h before and 2,000 mL for 24 h after the procedure and one group who received 2,000 mL of tap water only for 24 h after the procedure). The CIN incidence rates were 5.0, 7.5, and 5.0%, respectively, and no significant difference was found among the 3 groups.…”
Section: Level Of Evidence: II / Grade Of Recommendation: C1mentioning
confidence: 99%
“…The incidence of CIN was 6.9% in the drinking water group and 7.3% in the physiological saline group, and no significant difference was found between the two groups. 210 In a study on patients with normal renal function (SCr <110 μmol/L≈1.24 mg/dL) undergoing scheduled CAG or PCI, the preventive effect of the administration of 1 mL/kg/h of physiological saline solution 12 h before and 24 h after the procedure on CIN onset was compared to two drinking load groups (one group who received 500 mL of tap water for 2 h before and 2,000 mL for 24 h after the procedure and one group who received 2,000 mL of tap water only for 24 h after the procedure). The CIN incidence rates were 5.0, 7.5, and 5.0%, respectively, and no significant difference was found among the 3 groups.…”
Section: Level Of Evidence: II / Grade Of Recommendation: C1mentioning
confidence: 99%
“…The direct toxicity of contrast agents to renal tubular epithelial cells, leading to apoptosis and necrosis and resultant loss of function. Accordingly, indirect mechanisms are associated with ischemic injury due to renal vasomotor alteration implicated by vasoactive agents like nitric oxide, prostaglandins and endothelin, since following a diminution in nitric oxide creation, the ischemia will increase and will lead to nephrotoxicity (20)(21)(22)(23). Numerous studies showed the value of endothelin, which has been detected to increase after contrast media exposure (24).…”
Section: Pathophysiology Of Contrast-associated Acute Kidney Injurymentioning
confidence: 99%
“…The authors concluded that oral hydration is as safe and effective as intravenous prophylaxis. Akyuz and colleagues [ 41 ] exclusively included subjects with normal or moderately impaired kidney function (CKD stages 1-2). All subjects had at least one CIN high risk factor such as higher age, diabetes, heart failure, and anemia.…”
Section: Prevention Using Crystalloidsmentioning
confidence: 99%
“…All subjects had at least one CIN high risk factor such as higher age, diabetes, heart failure, and anemia. CIN occurred with comparable frequencies in both groups [ 41 ]. Although oral hydration may appear as a more feasible option, at first sight, several questions remain unanswered.…”
Section: Prevention Using Crystalloidsmentioning
confidence: 99%